2014
DOI: 10.1177/1660.18174
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Detecting Circulating Hepatocellular Carcinoma Cells in Peripheral Blood of Hepatocellular Carcinoma Patients by Nested Reverse Transcription-polymerase Chain Reaction and its Clinical Value: A Retrospective Study

Abstract: The presence of alpha-fetoprotein messenger RNA in peripheral blood may be an indicator of circulating hepatocellular carcinoma cells, which might predict hematogenous spreading metastasis in patients with hepatocellular carcinoma and may be a poor prognostic factor for hepatocellular carcinoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Most cases of HCC in whom AFPmRNA was detected were HBV seropositive (66.7%) compared to a previous study which indicated no association between AFPmRNA and hepatitis B infection (14). This is probably due to the high seroprevalence of HBV in Sudan.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Most cases of HCC in whom AFPmRNA was detected were HBV seropositive (66.7%) compared to a previous study which indicated no association between AFPmRNA and hepatitis B infection (14). This is probably due to the high seroprevalence of HBV in Sudan.…”
Section: Discussionmentioning
confidence: 54%
“…Nested RT-PCR was conducted and samples were analyzed by electrophoresis on a 15% polyacrylamide gel and stained with ethidium bromide for the specific bands. The design of external and inner pairs of primers were taken from previous research as follows (14).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the content of AFP in serum has a significant correlation with the number of cancer cells and degree of differentiation of liver cancer. Serum AFP content is directly proportional to tumor diameter, and as its content increases, recurrence and metastasis are more likely to occur (32). Therefore, the content of AFP in serum has important value for the diagnosis and treatment of liver cancer and the prediction of recurrence.…”
Section: Figurementioning
confidence: 99%
“…Finally, circulating tumor cells (CTCs) recruited in peripheral blood were identified as a marker of hematogenous spread in various solid tumors [11]. So far, their predictive and prognostic value has been proven in breast [12], colorectal [13], lung [14], esophageal [15], liver [16], pancreatic [17], and prostate cancers [18]. Recently, the presence of positive CTCs was associated with deep myometrial invasion and lymph node positivity in endometrial cancer [19].…”
Section: Introductionmentioning
confidence: 99%